(untitled) (Research, Society and Development, 2022)
Technology is a tool that provides procedural facilities in order to solve routine problems and, in this way, improve human life. Within this aspect, the Digital Information and Communication Technologies - TDIC’s, can be understood as a diversity of interconnected technological resources that use hardware, software, devices and other technologies that facilitate informational and communicative processes. Thus, the research aimed to: Understand the perceptions of high school teachers from a public school, who use TDIC’s in the classroom. This qualitative research was characterized as an exploratory study. The research subjects were teachers of a High School, of the State Education Network located in the municipality of Pedra Branca, Ceará. Data collection took place through semi-structured interviews, and soon after, the data were analyzed based on pre-defined categorization, guided by the specific objectives of the research. The analyzes indicate the need for a qualified education professional in computer science within schools in order to efficiently and satisfactorily manage the use of these technologies. It is understood, then, that by training and qualifying teachers to use the new technologies, as well as computerizing the classrooms with technological resources, they provide a great development in the construction of the teaching and learning process.